Jack's bed - Rickards, Lynne; Beardshaw, Rosalind (New York : Crabtree Pub., 2006)
Jack has a difficult time staying in his own bed throughout the night, until a special toy leopard appears to keep him company.
School Library Journal.
2.7
K-3
Keywords: Bedtime -- Juvenile fiction; Toys -- Juvenile fiction; Bedtime -- Fiction; Toys -- Fiction; Bedtime -- Fiction; Toys -- Fiction; Readers (Elementary).